Hygiene Sanitasi Pedagang dan Identifikasi Keberadaan Bakteri Salmonella Thypi pada Rujak Buah - Yusa Feriyadi; Sri Ratna Astuti; Ana Yustika; Aprin Wahyu Wijayanti; Ana Khoirul Ummah (STIKES HAKLI Semarang, 2025)
Salmonella typhi bacteria are pathogenic bacteria that can cause typhoid fever, one of the endemic diseases in Indonesia that is still a public health problem to this day. This disease is often associated with poor environmental conditions and low implementation of hygiene sanitation, especially in the handling of food sold in traditional markets. In 2016, Semarang City ranked 9th out of 35 districts/cities in Central Java as the area with the most typhoid fever cases. This study aims to describe the sanitary hygiene of traders as well as identify the presence of Salmonella typhi bacteria in fruit rujak sold at Karangayu Market, Semarang City. The type of research used is a laboratory experiment with a total sampling method. All samples of fruit rujak obtained from traders in the market were examined using microbiological tests. The results of the study showed that there was one sample of fruit rujak that was contaminated with Salmonella typhi. This contamination has the potential to arise due to several factors, including the cleanliness of tools and materials, the water sources used, the personal hygiene of traders, and inadequate environmental conditions around the point of sale. These findings underscore the importance of increasing traders' awareness of good sanitation practices and surveillance from health agencies to prevent the spread of typhoid fever through food. Routine education, the provision of clean water facilities, and periodic laboratory examinations are needed as a preventive effort. This research is expected to be a reference for local governments in establishing environmental and food safety-based disease control policies.